2019
DOI: 10.1177/1747493019838760
|View full text |Cite
|
Sign up to set email alerts
|

14th International Symposium on Thrombolysis, Thrombectomy and Acute Stroke Therapy: Proceedings and summary of discussions

Abstract: The 14th International Symposium on Thrombolysis, Thrombectomy and Acute Stroke Therapy (TTST) took place in Houston, Texas on 21-22 October 2018. Attended by 150þ invited global experts, the objectives of TTST 2018 were to explore the changing landscape of acute ischemic stroke therapy and to address current controversies in thrombolysis and thrombectomy, including expanding access and systems of care with global relevance. This article summarizes the proceedings of TTST 2018. The key points of each session a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…In any case, time remains fundamental with regard to the results that can be obtained 14 . In the present study, acute-phase therapeutic interventions were performed on 32.44% of the stroke patients treated at HEC, which is a high rate even by international standards 25 , 26 . Nevertheless, this demonstrates that there is a need to expand VT and MT care, considering the efficiency of these therapies not only for reducing mortality but also for reducing the disabilities acquired by patients 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In any case, time remains fundamental with regard to the results that can be obtained 14 . In the present study, acute-phase therapeutic interventions were performed on 32.44% of the stroke patients treated at HEC, which is a high rate even by international standards 25 , 26 . Nevertheless, this demonstrates that there is a need to expand VT and MT care, considering the efficiency of these therapies not only for reducing mortality but also for reducing the disabilities acquired by patients 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of intravenous thrombolysis (IVT) and mechanical thrombectomies (MTs) in acute stroke patients varied greatly within Asia. Earlier studies showed greater use in East Asia compared to other Asian regions [ 37 ]. In Asia, most countries adopted the dosage of 0.9 mg/kg while in Japan, Pakistan, Vietnam, and in some hospitals in the Philippines and India 0.6 mg/kg was the standard dose [ 38 ].…”
Section: Treatment Approaches and Infrastructure For Hyperacute Strok...mentioning
confidence: 99%